2004
DOI: 10.1097/01.sla.0000132986.75257.19
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Bioartificial Liver Support Systems

Abstract: Bioartificial liver therapy for bridging patients with ALF to liver transplantation or liver regeneration is promising. Its clinical value awaits further improvement of BAL devices, replacement of hepatocytes of animal origin by human hepatocytes, and assessment in controlled clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(90 citation statements)
references
References 115 publications
0
89
0
1
Order By: Relevance
“…However, animal models make extension to the human clinical scenario difficult due to, amongst other reasons, species differences in response to test substances, the degree of reversibility, the disease process duration and the degree of involvement of other organ systems [24,25]. The ¾-partial liver resection in rats is an attractive model in that it is welldescribed, technically feasible, highly reproducible, non-toxic yet severe, but reversible within a time period sufficient to enable study.…”
Section: Discussionmentioning
confidence: 99%
“…However, animal models make extension to the human clinical scenario difficult due to, amongst other reasons, species differences in response to test substances, the degree of reversibility, the disease process duration and the degree of involvement of other organ systems [24,25]. The ¾-partial liver resection in rats is an attractive model in that it is welldescribed, technically feasible, highly reproducible, non-toxic yet severe, but reversible within a time period sufficient to enable study.…”
Section: Discussionmentioning
confidence: 99%
“…12), showed significant improvement of survival time in ALF animal models (13,14,33), and proved to be safe in a phase I clinical trial conducted in Italy (38)(39)(40). In this era of organ donor shortage, many acute liver failure (ALF) patients die on the liver transplantation Logistical problems may, however, affect the outcome of BAL treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition the biotransformation capacity of the hepatocytes within the bioreactor was retained for at least a week, providing a good model for metabolite investigations from slowly metabolised drugs [35]. The activity of CYP3A4 was demonstrated in the 3D bioreactor system by monitoring the metabolism of atorvastatin acid (ATA) to its 2-and 4-hyroxylated metabolites [36], and for HepaRG cells in the 3D system by monitoring midazolam, which indicated that CYP3A4 activity was retained for up to 2 weeks [48]. This retention of CYP3A4 activity is longer than that currently available in other in vitro models.…”
Section: Use Of Bals In Dmpk Studiesmentioning
confidence: 99%
“…Blood is ultrafiltered and pumped through fibres, with plasma flowing through the ECS. This direct interaction allows cellular processes to occur before the ultrafiltrate is filtered by a dual membrane to remove cells and cellular debris and returned back into the blood stream [48].…”
Section: Device Designs and Functionalitymentioning
confidence: 99%